Techno Economical Evaluation for Energy Analysis in AA6061 during Cold Metal Transfer Welding. (2018) - Pavan Kumar, N.; Chinnadurai, T.; Vendan, S. Arungalai; Sivashanmugam, N.
Abstract: Two critical factors demanding precedence in production firms are the rate of productivity and the total cost incurred. In the competitive cosmic manufacturing sector, with the advent of sophisticated materials, the conventional materials in various parts are frequently being replaced. Under such circumstances, it is imperative to investigate the materials weldability features when it is subjected to real time applications. In this study Al 6061 alloy subjected to cold metal transfer (CMT). Experimental trails have been carried out based on design of experiments, Energy incurred in the various trails of the different parametrical sets are recorded and the corresponding changes in the micro structural behaviours and the depth of penetration is examined. This research study is expected to provide an insight into the energy and its associated concepts which alters the choice of the manufacturing process.